Pengaruh Diameter Katup Pengantar Dan Tinggi Angkat Terhadap Efisiensi Pompa Hidram 3 Inci - Jafri, Muhamad; Nurhayati, Nurhayati; Rimas, Dedy Isman (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2021)
This study aims to analyze the effect of valve diameter and delivery head on hydram pump. The method used is experiment on specimens, and analysis using mathematical equations in hydram pump theory. The data measured are the flow of water in, discharge of waste water, and discharge of water out. The independent variables in this study were the diameter of the introductory valve, namely 2.0 inches, 2.25 inches, 2.50 inches, 2.75 inches, and delivery head, namely 3 m, 5 m, 7 m. Furthermore, analysis of the head loss and the efficiency of the D'Aubuisson hydram pump was carried out. The results showed that the diameter of the delivery valve and the delivery head had an effect on the effect of the hydram pump. The highest hydram pump occurs at a delivery valve diameter of 2.5 inches and a delivery head of 5 m at 55.21%. While the lowest occurred at a delivery head of 3 m and a diameter of 2.0 inch delivery valve at 13.75%.